E-Government dengan Pemanfaatan Web OpenSID dalam Pelayanan Publik di Nagari Tanjung Haro Sikabu-kabu Padang Panjang - Hazid Jalma; Roni Ekha Putera; Kusdarini Kusdarini (Universitas Muhammadiyah Gorontalo, 2019)
As a form of e-Government development initiative, Nagari Tanjung Haro Sikabu-kabu Padang Panjang has an initiative in the form of using the OpenSID web application. But in its implementation, there are still shortcomings and problems in the OpenSID implementation process. This research was conducted using qualitative descriptive methods. Data were collected through interviews with respondents selected based on purposive sampling technique, documents on the use of OpenSID web and observing the use of OpenSID web on improving public services. The study show that the use of the OpenSID web in improving public services has gone well, can be seen from the dimensions of public sector web analysis. Utilization of the OpenSID web has various information and is managed well with the PPID. The impact of public services that can be felt from the use of the OpenSID web is to easily obtain nagari information, information on public service processes and public services that can be resolved quickly because of population data that already exists on the OpenSID server. However, the utilization of the OpenSID website is still not running optimally. This is because some of the information contained in the content is non-updated information and some information does not yet exist.Sebagai bentuk inisiatif pengembangan e-Government, Nagari Tanjung Haro Sikabu-kabu Padang Panjang memiliki inisiatif dalam bentuk menggunakan aplikasi web OpenSID. Namun dalam implementasinya, masih ada kekurangan dan masalah dalam proses implementasi OpenSID. Penelitian ini dilakukan dengan menggunakan metode deskriptif kualitatif. Data dikumpulkan melalui wawancara dengan responden yang dipilih berdasarkan teknik purposive sampling, dokumen tentang penggunaan web OpenSID dan mengamati penggunaan web OpenSID untuk meningkatkan layanan publik. Studi ini menunjukkan bahwa penggunaan web OpenSID dalam meningkatkan layanan publik telah berjalan dengan baik, dapat dilihat dari dimensi analisis web sektor publik. Pemanfaatan web OpenSID memiliki berbagai informasi dan dikelola dengan baik dengan PPID. Dampak dari layanan publik yang dapat dirasakan dari penggunaan web OpenSID adalah dengan mudah mendapatkan informasi nagari, informasi tentang proses layanan publik dan layanan publik yang dapat diselesaikan dengan cepat karena data populasi yang sudah ada di server OpenSID. Namun, pemanfaatan situs web OpenSID masih belum berjalan optimal. Ini karena beberapa informasi yang terkandung dalam konten adalah informasi yang tidak diperbarui dan beberapa informasi belum ada.